Correlation between Intraoperative Fluid Administration and Outcomes of Pancreatoduodenectomy - Xuefeng Cao; Xixiu Wang; Baolei Zhao; Lingqun Kong; Lei Zhou; Wentao Zhu; Xutao Lin; Qiangpu Chen; Xingyuan Zhang (Gastroenterology Research and Practice)
Background. Intraoperative fluid (IOF) administration plays an important role during major abdominal surgery although increased fluid intake can adversely influence postoperative outcomes. However, the effect of the IOF rate on the outcomes of pancreatoduodenectomy (PD) is unclear. Methods. 151 patients, who underwent PD at Binzhou Medical University Hospital between January 2010 and May 2017, were categorized into three groups according to IOF rates (ml/kg/hr): restricted (<10, n=47), standard (10–15, n=76), and liberal (>15, n=28). Results. The overall postoperative morbidity was 56.95%. The incidence of postoperative pancreatic fistula (POPF) was 11.26%. The in-hospital mortality rate was 7.28% with the most common cause being grade C POPF and secondary intra-abdominal infections. The patients in the liberal group had significantly higher incidences of POPF (25%) and respiratory complications (21.43%). The other outcome parameters such as recovery of bowel function, hospital stay, and postoperative daily drainage were similar among the groups. Multivariable analysis confirmed the IOF rate to be most strongly associated with POPF (odds ratio: 5.195, confidence interval: 1.142–23.823, P=0.023) and respiratory complications (odds ratio: 7.302, confidence interval: 0.676–58.231, P=0.025). Conclusions. The IOF rate significantly affects the incidence of POPF and respiratory complications after PD. Careful patient-oriented fluid therapy may help to prevent these complications.